HISTORY AND NEW RESULTS OF ARCHAEOLOGICAL RESEARCH IN THE MOORING FORTRESSES OF MOMINABAD (TAMADDUN NURI JURNALI, 2024)
The article provides information on the history of research conducted in the Mominabad burial mounds located in the middle reaches of the Zarafshan River, as well as on the archaeological research conducted in recent years and the results achieved. As a result of the history of the study of the Mominabad Bronze Age graves conducted by A. Askarov, information is provided that Bronze Age communities lived in this area. As a result of recent research, newly discovered archaeological monuments and burial mounds were scientifically analyzed. As a result of the archaeological excavations of the Kochkorkotan, Tolmazor, and Chiroqtash burial mounds, new scientific information was obtained on the area.